Corneal Ectasia Risk And Percentage Tissue Altered In Myopic Patients Presenting For Refractive Surgery - Ong HS (Dove Medical Press, 2019)
Hon Shing Ong,1–3 Mohamed Farook,1 Benjamin Boon Chuan Tan,1 Geraint P Williams,1,2 Marcony R Santhiago,4,5 Jodhbir S Mehta1–3,6 1Department of Corneal and External Diseases, Singapore National Eye Centre, Singapore, Singapore; 2Tissue Engineering and Stem Cell Group, Singapore Eye Research Institute, Singapore, Singapore; 3SingHealth Duke-NUS Ophthalmology and Visual Sciences Academic Clinical Programme, Duke-NUS Graduate Medical School, Singapore, Singapore; 4Department of Ophthalmology, Federal University of Rio de Janeiro, Rio de Janeiro, Brazil; 5Department of Ophthalmology, University of Sao Paulo, Sao Paulo, Brazil; 6School of Material Science and Engineering, Nanyang Technological University, Singapore, SingaporeCorrespondence: Hon Shing Ong; Jodhbir S MehtaDepartment of Corneal and External Diseases, Singapore National Eye Centre, 11 Third Hospital Avenue, Singapore168751, SingaporeTel +65 6227 7255Email honshing@gmail.com; jodmehta@gmail.comPurpose: A percentage tissue altered (PTA) score of ≥40% has been advocated as an independent indicator of post-operative ectasia risk following laser in-situ keratomileusis (LASIK). This study was performed to test the hypothesis that refractive procedures, such as laser-assisted sub-epithelial keratectomy (LASEK) or small incision lenticule extraction (SMILE), may alter the range of PTA, within which refractive corneal surgery can be safely performed.Setting: Refractive department, tertiary ophthalmic hospital.Design: Retrospective observational study.Methods: Review of case notes was performed for patients who presented for refractive surgeries, other than LASIK. To determine the risk of corneal ectasia for each patient prior to refractive surgery, we estimated what each patient’s PTA would have been if they had undergone LASIK. The Randleman Ectasia Risk Score System (ERSS) was also calculated.Results: 114 eyes (66 patients) were included. 94 eyes underwent SMILE. 20 eyes underwent LASEK. A significant proportion of eyes had PTA ≥40% – SMILE eyes: up to 31.9%, LASEK eyes: up to 60.0% (at presumed LASIK flap of 120 μm). The maximum calculated PTA was up to 47.9% in the SMILE group and up to 51.5% in the LASEK group. Using ERSS, 12.8–16% of SMILE eyes and 15.0–80.0% of LASEK eyes would have been considered to have moderate-to-high ectasia risk. No post-surgical ectasia was observed at 3 years.Conclusion: SMILE and LASEK alter the range of PTA, within which corneal refractive surgery may be performed with a lower risk of developing post-operative corneal ectasia; a safe PTA threshold needs to be determined for these procedures before recommendations for clinical practice can be made.Keywords: percentage tissue altered, ectasia, refractive surgery, laser in situ keratomileusis, laser-assisted sub-epithelial keratectomy, small incision lenticule extraction